ECONOMIC IMPORTANCE OF ORGANIZING TRANSPORT LOGISTICS - Egamberdiyev Shavkatbek; Shukurov Umidjon (Лучшие интеллектуальные исследования, 2024)
Annotation. The article examined the economic significance of the organization of the logistics transport logistics system. An idea to increase economic importance and reduce costs in particular, goods such as shopping, storage, packaging and vehicles issues related to important elements of the movement were considered. Logistics the problems faced by the companies were analyzed. Introduced in logistics identified the advantages and disadvantages of technologies and their use proposals were made to improve efficiency.